Regulatory Fibroblast‐Like Synoviocytes Cell Membrane Coated Nanoparticles: A Novel Targeted Therapy for Rheumatoid Arthritis. Issue 4 (12th December 2022) - Liu, Yuan; Rao, Peishi; Qian, Hongyan; Shi, Yesi; Chen, Shiju; Lan, Jingying; Mu, Dan; Chen, Rongjuan; Zhang, Xinwei; Deng, Chaoqiong; Liu, Gang; Shi, Guixiu
Abstract: Fibroblast‐like synoviocytes (FLS) are the main cell component in the inflamed joints of patients with rheumatoid arthritis (RA). FLS intimately interact with infiltrating T cells. Fibroblasts have potent inhibitory effects on T cells, leading to the resolution of inflammation and immune tolerance. However, this "regulatory" phenotype is defect in RA, and FLS in RA instead act as "proinflammatory" phenotype mediating inflammation perpetuation. Signals that orchestrate fibroblast heterogeneity remain unclear. Here, it is demonstrated that different cytokines can induce distinct phenotypes of FLS. Interferon‐gamma (IFN‐ γ ) is pivotal in inducing the regulatory phenotype of FLS (which is termed FLS reg ) characterized by high expressions of several inhibitory molecules. Rapamycin enhances the effect of IFN‐ γ on FLS. Based on the characteristics of FLS reg, a novel biomimetic therapeutic strategy for RA is designed by coating cell membrane derived from FLS reg induced by IFN‐ γ and rapamycin on nanoparticles, which is called FIRN. FIRN show good efficacy, stability, and inflammatory joint targeting ability in an RA mouse model. The findings clarify how fibroblast phenotypes are modulated in the inflammatory microenvironment and provide insights into novel therapeutic designs for autoimmune diseases based on regulatory fibroblasts. Abstract : This study demonstrates an in vitro induction method for regulatory fibroblast‐like synoviocytes (FLS) phenotype (FLS reg ) by interferon‐gamma and rapamycin. Based on the characteristics of FLS reg, a novel biomimetic therapeutic strategy for rheumatoid arthritis (RA) is proposed by coating cell membrane derived from FLS reg on nanoparticles, which shows good efficacy, stability, and inflammatory joint targeting ability in the RA mouse model.